Evaluation of the Impact of Implementing the Emergency Medical Services Traumatic Brain Injury Guidelines in Arizona: The Excellence in Prehospital Injury Care (EPIC) Study Methodology. (11th August 2014) - Spaite, Daniel W.; Bobrow, Bentley J.; Stolz, Uwe; Sherrill, Duane; Chikani, Vatsal; Barnhart, Bruce; Sotelo, Michael; Gaither, Joshua B.; Viscusi, Chad; Adelson, P. David; Denninghoff, Kurt R.; Newgard, Craig D.
Abstract Traumatic brain injury (TBI) exacts a great toll on society. Fortunately, there is growing evidence that the management of TBI in the early minutes after injury may significantly reduce morbidity and mortality. In response, evidence‐based prehospital and in‐hospital TBI treatment guidelines have been established by authoritative bodies. However, no large studies have yet evaluated the effectiveness of implementing these guidelines in the prehospital setting. This article describes the background, design, implementation, emergency medical services (EMS) treatment protocols, and statistical analysis of a prospective, controlled (before/after), statewide study designed to evaluate the effect of implementing the EMS TBI guidelines—the Excellence in Prehospital Injury Care (EPIC) study (NIH/NINDS R01NS071049, "EPIC"; and 3R01NS071049‐S1, "EPIC4Kids"). The specific aim of the study is to test the hypothesis that statewide implementation of the international adult and pediatric EMS TBI guidelines will significantly reduce mortality and improve nonmortality outcomes in patients with moderate or severe TBI. Furthermore, it will specifically evaluate the effect of guideline implementation on outcomes in the subgroup of patients who are intubated in the field. Over the course of the entire study (~9 years), it is estimated that approximately 25, 000 patients will be enrolled.